Operational Experiences and Lessons Learned at the Climate Migration Development Nexus : A World Bank Portfolio Review with a Focus on Sub-Saharan Africa - Rigaud, Kanta Kumari; Heuser, Silke; Abu-Ata, Nathalie; Arora, Anmol (World Bank, Washington, DC, 2021)
This portfolio review examines the design features of World Bank interventions operating at the intersection of climate-migration-development with the aim to draw actionable insights and recommendations. The review identifies 165 projects against a set of mobility-related keywords with commitments totaling to US$197.5 billion for the period from 2006 to 2019 classified into two thematic categories: migration-focused projects that cater specifically to migrants, refugees, displaced, or the host-communities as their beneficiaries; and development focused projects which have a broader remit but include within its components a focus on mobility. The Inter-Governmental Panel of Climate Change (IPCC) risk framework is used to assess how project interventions can be effective and deliver durable outcomes—through cross-learning across the two categories of projects. Climate change is emerging as a potent driver of mobility-immobility dynamics, and it carries wider development implications that cannot be ignored. The World Bank flagship report Groundswell: Preparing for Internal Climate Migration (Rigaud et al. 2018) projects that by 2050 just over 143 million people across Sub-Saharan Africa, Latin America and South Asia could be forced to move within their own countries to escape the slow onset impacts of climate change. The review underscores the wealth of good practice that can inform projects to innovate and devise more integrative solution by sharpening attention to underlying causes of migration along with immediate and urgent needs of the stakeholders; and where possible to design interventions that are proactive in anticipating future climate risks from slow- and rapid-onset climate impacts.